2009
DOI: 10.3844/jcssp.2009.435.439
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Corrosion-Damaged Reinforced Concrete Beams with Glass Fiber Reinforced Polymer Laminates

Abstract: Problem statement:This study showed the results of an experimental investigation on the strengthening of corrosion damaged reinforced concrete beams with unidirectional cloth glass fiber reinforced polymer (UDCGFRP) laminates. Approach: All the beam specimens 150×250×3000 mm were cast and tested for the present investigation. One beam specimen was neither corroded nor strengthened to serve as a reference. Two beams were corroded to serve as a corroded control. A reinforcement mass loss of approximately 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…FRP dapat digunakan untuk memperkuat atau merehabilitasi balok beton bertulang dengan bukaan pada balok (Mondal & Gautam, 2011). Penggunaan FRP pada struktur yang telah mengalami penurunan kekuatan akibat korosi di mana balok yang diperkuat dengan FRP akan meningkatkan kekakukan, batas leleh dan kekuatan batasnya (Rose et al, 2009). Penggunaan GFRP tipe lembaran sebagai perkuatan pada balok beton bertulang yang telah terbebani hingga leleh tulangan memiliki kapasitas lentur yang lebih tinggi dari balok aslinya (Djamaluddin & Hino, 2011).…”
Section: Pendahuluanunclassified
“…FRP dapat digunakan untuk memperkuat atau merehabilitasi balok beton bertulang dengan bukaan pada balok (Mondal & Gautam, 2011). Penggunaan FRP pada struktur yang telah mengalami penurunan kekuatan akibat korosi di mana balok yang diperkuat dengan FRP akan meningkatkan kekakukan, batas leleh dan kekuatan batasnya (Rose et al, 2009). Penggunaan GFRP tipe lembaran sebagai perkuatan pada balok beton bertulang yang telah terbebani hingga leleh tulangan memiliki kapasitas lentur yang lebih tinggi dari balok aslinya (Djamaluddin & Hino, 2011).…”
Section: Pendahuluanunclassified
“…Sultan, conducted research the effect marine environment to the concrete beams Strengthened Using GFRP Sheet. The result of this study also showed that for areas closer to the sea has a greater effect in terms decreasing flexural capacity of the beam which has corrosion on beam [4,5]. FRP materials composed of fibers and matrix, in which the fibers provide strength and rigidity while the matrix holds the fibers together, protect the fibers from abrasion and corrosion and also transfers the pressure to the fiber [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of GFRP in the form of sheets is currently very common because the price is relatively more economical when compared to other types. Beams reinforced with FRP will increase stiffness, yield limit, and limit strength in studies of reinforcement repairs that have corroded the beam [18]. Other research related to the use of GFRP in beams shows that beams reinforced with FRP as flexural reinforcement in reinforced concrete beams can increase the load up to 75.15% and increase the maximum deflection.…”
Section: Introductionmentioning
confidence: 99%